2015
DOI: 10.1093/omcr/omv008
|View full text |Cite
|
Sign up to set email alerts
|

Severe short stature and Wolf-Hirschhorn syndrome: response to growth hormone in two cases without growth hormone deficiency

Abstract: Wolf-Hirschhorn syndrome (WHS) is a rare congenital disorder occurring in approximately 1/50 000 births, with marked pre- and postnatal growth failure. WHS results from the hemizygous deletion encompassing the 4p16.3 region. This report of two children with WHS shows that growth hormone treatment in selected children with WHS and severe short stature may have a substantial effect on long-term growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Like others ( 9 ), we found that GV approximated mean population GV when she was treated with GH from 3 years 8 months till 8 years 8 months old ( Fig. 2 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Like others ( 9 ), we found that GV approximated mean population GV when she was treated with GH from 3 years 8 months till 8 years 8 months old ( Fig. 2 ).…”
Section: Discussionsupporting
confidence: 87%
“…Among Asians, growth of 34 WHS Japanese children 0–17 years were collated and plotted against local norms ( 7 ). Both data sets, as well as data from other case reports ( 8 , 9 ), describe marked growth retardation among children with WHS. However, information on pubertal growth and final height (FH) among WHS children was lacking.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Growth hormone deficiency (GHD) is a type of growth disorder which is caused by growth hormone (GH) deficiency or inadequate secretion of GH due to hypothalamus or anterior pituitary dysfunction ( 1 , 2 ). It is a common disorder of the endocrine system in children.…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal malformations have been reported in both the axial and appendicular skeleton. Delayed bone age has been widely recognized as a common feature of WHS (Austin, Gunn, & Jefferies, 2015; Gonzalez et al, 1981; Opitz, 1995), although there has been no publications investigating bone fragility. Delayed and secondary centers of ossification and pseudoepiphyses have been shown in hand radiographs (Beluffi & Savasta, 2010; Opitz, 1995).…”
Section: Discussionmentioning
confidence: 99%